Method for converting oily quantum dots into water phase and water-phase quantum dots thereof
By self-assembly preparing seed microspheres wrapped in oily quantum dots in the amphiphilic polymer, and adding regulators and hydrophilic ligands to the aqueous solution, the oily quantum dots are converted into aqueous phase, solving the water phase quantum in the prior art The problems of low point fluorescence efficiency and low yield of the aqueous phase have achieved efficient and stable mass production.
Patent Information
- Application Number
- CN202410585379.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-11
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art method of converting oily quantum dots to aqueous phase, the fluorescence efficiency of the aqueous quantum dots is low, the yield of the aqueous phase is also low, and the process is difficult to control, the experimental/production failure rate is high, and it is difficult to mass produce.
By self-assembly, seed microspheres wrapped with oily quantum dots are prepared in the amphiphilic polymer, and a regulator and hydrophilic ligand are added to the aqueous solution to form a reaction mixture, so that the oily quantum dots are converted into the aqueous phase and obtain high fluorescence Efficient water phase quantum dots.
It improves the fluorescence efficiency of aqueous quantum dots and the yield of oily quantum dots to aqueous phase, simplifies operation steps, improves the success rate of experiments/production, and is suitable for mass production.
Smart Images

Figure CN119432364A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of quantum dots, and specifically relates to a method for converting oily quantum dots into aqueous phase and aqueous phase quantum dots thereof. Background Art
[0002] Quantum dots, also known as semiconductor nanocrystals, are a new type of semiconductor nanomaterial with a size of 1-10nm. Due to the quantum size effect and dielectric confinement effect, they have unique photoluminescence (PL) and electroluminescence (EL) properties. Compared with traditional organic fluorescent dyes, quantum dots have high quantum yield, high photochemical stability, not easy to photolyze, as well as wide excitation, narrow emission, high color purity, and the luminescent color can be adjusted by controlling the size of quantum dots. Excellent optical properties have broad application prospects in the field of display technology. At the same time, with the help of different types of quantum dot components and different quantum dot contents, multiple different luminescent bands (colors) can be formed, which have the function of marking / coding, so they can also be widely used in biomarkers, disease diagnosis, tracers, solid-phase chips, liquid-phase chips, immunochromatography, Raman scattering and other fields.
[0003] At present, the synthesis of quantum dots mainly adopts the chemical solution growth method. If the quantum dots prepared by the chemical solution growth method are not modified by additional ligands, they are usually oily quantum dots because the surface of the quantum dots has lipophilic groups (such as organic acids such as oleic acid, organic amines such as oleylamine, organic phosphines such as trioctylphosphine, and thiols such as dodecanethiol). However, quantum dots are used in the biological field and the field of aqueous phase tracers, and they need to be water-soluble; or in some methods of synthesizing quantum dot microspheres, the oily quantum dots need to be transferred to the aqueous phase first. In the prior art methods of transferring oily quantum dots to water phase: 1. When transferring to water phase in aqueous solution, the fluorescence efficiency of water phase quantum dots is low and even easily quenched, and the yield of water phase transfer is low; 2. When transferring to water phase in oil-in-water droplets, the fluorescence efficiency of water phase quantum dots is improved compared with the prior art 1, but the fluorescence efficiency of water phase quantum dots is still relatively low, and the yield of water phase transfer needs to be improved; 3. When transferring to water phase in oil phase, it is necessary to continuously add polar solvents such as ethanol during the reaction to avoid precipitation of quantum dots during the process of transferring to water phase. This process is difficult to control, the experimental / production failure rate is very high, and it is difficult to mass produce, and the yield of water phase transfer is low.
[0004] In view of this, the present application provides a method for transferring oily quantum dots to water phase and its water phase quantum dots, wherein the water phase quantum dots have high fluorescence efficiency and high yield of oily quantum dots transferred to water phase. Summary of the invention
[0005] The purpose of the present application is to provide a method for transferring oily quantum dots to an aqueous phase and its aqueous phase quantum dots, wherein the aqueous phase quantum dots have high fluorescence efficiency and a high yield of oily quantum dots transferred to an aqueous phase.
[0006] In a first aspect of the present application, a method for transferring oily quantum dots into an aqueous phase is provided, the method comprising:
[0007] S1, preparation of seed microspheres containing oily quantum dots encapsulated in amphiphilic polymers by self-assembly;
[0008] S2, dissolving the seed microspheres in an aqueous solution, and adding a regulator to reduce the polarity of the outer surface of the seed microspheres or reduce the polarity of the aqueous solution;
[0009] S3, adding a hydrophilic ligand into S2 to form a reaction mixture, wherein the hydrophilic ligand combines with the oily quantum dots to transfer the oily quantum dots to a water phase, thereby obtaining water phase quantum dots.
[0010] In some embodiments, in step S1, the self-assembly refers to the amphiphilic polymer and the oily quantum dots, through physical action, to form oily quantum dot seed microspheres encapsulated in the amphiphilic polymer (also called amphiphilic polymer shell).
[0011] Further, specifically, the self-assembly refers to mixing an amphiphilic polymer, oily quantum dots, a non-polar solvent, water and an oil-in-water surfactant, emulsifying to form oil-in-water microdroplets, evaporating / volatizing the non-polar solvent (internal phase solvent of the microdroplets), and forming seed microspheres containing multiple oily quantum dots encapsulated in the amphiphilic polymer.
[0012] The dielectric constant of the non-polar solvent is 1.5-10, and the non-polar solvent can evaporate / volatize at a temperature lower than the boiling point of water. The HLB value of the water-in-oil type surfactant is 8-18.
[0013] In some embodiments, the amphiphilic polymer includes a hydrophilic segment and a lipophilic segment, the hydrophilic segment is soluble in water solvent, and the lipophilic segment is soluble in non-polar solvent.
[0014] Furthermore, the hydrophilic segment includes at least one of polymaleic anhydride, maleic anhydride, polytetracarboxylic anhydride, polyacrylic acid, polyethylene glycol acrylic acid, polyethylene imine, polyimide, polyacrylamide, polyvinyl pyrrolidone, polyethylene glycol, polybutylene glycol, polypropylene glycol, polyethylene glycol monomethyl ether, polyvinyl alcohol, polyvinyl ether, and polyoxyethylene; the lipophilic segment includes at least one of C2-C30 aliphatic hydrocarbon groups (alkyl, alkenyl, alkynyl, etc.), polypropylene oxide, polystyrene, polyethylene, polypropylene, polybutadiene, polyisobutylene, polysiloxane, alcohol ester, polymethyl methacrylate, polyamino acid, and polylactic acid.
[0015] In some embodiments, the surface of the oily quantum dots has lipophilic groups.
[0016] Further, the lipophilic group is a lipophilic group on the surface of the quantum dot, or the lipophilic group is a lipophilic group modified on the surface of the quantum dot. Preferably, the lipophilic group is a lipophilic group on the surface of the quantum dot. The quantum dot comprises: at least one of IIB-VIA group quantum dots, IIIA-VA group quantum dots, IVA-VIA group quantum dots, IVA group quantum dots, IB-IIIA-VIA group quantum dots, IB-IIB-IVA-VIA group quantum dots, VIII-VIA group quantum dots, perovskite quantum dots and carbon quantum dots. The component containing the lipophilic group comprises: at least one of an organic acid, an organic amine, an organic phosphine, or a thiol.
[0017] In some embodiments, in step S2, in the aqueous solution, the concentration of the seed microspheres is 1-30 mg / ml. Preferably, in the aqueous solution, the concentration of the seed microspheres is 2-25 mg / ml. More preferably, in the aqueous solution, the concentration of the seed microspheres is 4-20 mg / ml.
[0018] In some embodiments, the aqueous solution further comprises: a dispersant. Adding a dispersant can improve the dispersibility of the seed microspheres in the aqueous solution, especially when the concentration of the seed microspheres is high. The dispersant is a hydroxyl polymer. The dispersant comprises: at least one of Tween 20, Tween 60, Tween 80, polyvinyl alcohol (PVA), and polyvinyl pyrrolidone (PVP).
[0019] In some embodiments, in step S2, a regulator is added so that the absolute value of the difference in polarity parameters between the inside and outside of the amphiphilic polymer shell is less than the absolute value of the difference in polarity parameters between the water phase quantum dots and the oil phase quantum dots. Preferably, in step S2, a regulator is added so that the absolute value of the difference in polarity parameters between the inside and outside of the amphiphilic polymer shell is 5-7.5. Preferably, in step S2, a regulator is added so that the absolute value of the difference in polarity parameters between the inside and outside of the amphiphilic polymer shell is 6-7.
[0020] Furthermore, the regulator includes at least one of an esterification catalyst, water-soluble aldehydes, water-soluble glycerol ethers, salts, and polar solvents.
[0021] Furthermore, the esterification catalyst includes: at least one of a water-soluble carbodiimide salt and a water-soluble imide salt. In the aqueous solution of step S2, the esterification catalyst is added to the seed microspheres in a mass ratio of 1:(2-10).
[0022] The esterification catalyst includes at least one of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate (HATU), N-hydroxysuccinimide (HoBT), N-hydroxysuccinimide (NHS), and N-hydroxysulfosuccinimide (Sulfo-NHS).
[0023] Furthermore, in the aqueous solution of step S2, the water-soluble aldehydes are added to the seed microspheres in a mass ratio of 1:(2-10), and the water-soluble aldehydes include at least one of glutaraldehyde, acetone aldehyde, acetaldehyde, succinaldehyde, and adipaldehyde.
[0024] Furthermore, in the aqueous solution of step S2, the mass ratio of the water-soluble glyceryl ether to the seed microspheres is 1:(2-10); the water-soluble glyceryl ether includes at least one of diglycidyl ether, allyl glycidyl ether, glycerol triglycidyl ether, and butanediol diglycidyl ether.
[0025] Furthermore, in the aqueous solution of step S2, the mass ratio of the salt added is 0.3-0.5 mg / ml; the salt includes: at least one of sodium chloride, potassium chloride, sodium bicarbonate, sodium carbonate, and calcium chloride.
[0026] Furthermore, the dielectric constant of the polar solvent is ≥18, and the mass ratio of the polar solvent to water added to the aqueous solution in step S2 is 1:(10-100). The polar solvent includes at least one of methanol, ethanol, ethylene glycol, diformamide, butanone, acetone, n-propanol, isopropanol, n-butanol, DMSO (dimethyl sulfoxide), tetrahydrofuran, and pyridine.
[0027] In some embodiments, in step S3, the hydrophilic ligand includes: a coordination group and a hydrophilic group, the coordination group can be connected to the surface of the oily quantum dots, and the hydrophilic group provides hydrophilicity to the quantum dots.
[0028] Further, the molecular weight of the hydrophilic ligand is 50-400. Preferably, the molecular weight of the hydrophilic ligand is 50-300.
[0029] Furthermore, the coordination group includes at least one of thiol, phosphate, amide, carboxyl, and amino; and the hydrophilic group includes at least one of hydroxyl, carboxyl, amino, imino, phosphate, quaternary ammonium, amide, and aldehyde.
[0030] In some embodiments, the mass ratio of the oily quantum dots to the hydrophilic ligands added to the reaction mixture is 1:(0.1-0.3.
[0031] In some embodiments, the reaction mixture is reacted at 10-50° C. and a stirring speed of 100-1000 rpm for 3-20 hours to obtain water-phase quantum dots.
[0032] In some embodiments, the reaction mixture containing water-phase quantum dots is purified to obtain water-phase quantum dots.
[0033] In some embodiments, the luminescence quantum yield of the water-phase quantum dots is ≥88%.
[0034] In some embodiments, the yield of the oily quantum dot-water-phase conversion is ≥85%.
[0035] In a second aspect of the present application, a water-phase quantum dot is provided, wherein the water-phase quantum dot is obtained by the above-mentioned method of converting the oil-phase quantum dot to the water phase.
[0036] In some embodiments, the luminescence quantum yield of the water-phase quantum dots is ≥88%.
[0037] The method of quantum dot-to-water phase conversion and the water-phase quantum dots of the present application have at least the following advantages compared with the prior art:
[0038] (1) The present application uses seed microspheres as a medium to transfer quantum dots to the water phase. Since the seed microspheres are all hydrophobic substances, water is difficult to penetrate into the seed microspheres during the reaction due to the repulsive effect of different polarities. After the water phase quantum dots that have successfully transferred to the water phase are expelled from the seed microspheres, the water phase quantum dots are bound to the surface with a large number of hydrophilic ligands, and their strong hydrophilicity forms a hydration layer for protection. The quantum dots rarely come into contact with water, and the fluorescence efficiency QY of the quantum dots is significantly improved.
[0039] (2) The coordination groups of the hydrophilic ligands have chelating and other interactions with the quantum dots in the amphiphilic polymer shell, and the hydrophilic ligands have a small molecular weight and can pass through the pores of the amphiphilic polymer shell, allowing the hydrophilic ligands to enter the interior of the amphiphilic polymer shell and continuously react and connect with the oily quantum dots, resulting in a high yield of quantum dots transferred to the water phase.
[0040] (3) In the process of quantum dots being transferred to the water phase of the present application, only quantum dots that are completely transferred to the water phase will be expelled from the seed microspheres, and quantum dots that are not completely transferred to the water phase will not be expelled from the seed microspheres due to the insufficient repulsive force. Therefore, the technical solution of the present application also plays a role in distinguishing whether the quantum dots are successfully transferred to the water phase. In the prior art, it is difficult to distinguish and screen quantum dots that are completely transferred to the water phase from quantum dots that are partially / incompletely transferred to the water phase.
[0041] (4) The operation steps are simple, the success rate of experiments / production is high, and it is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Combined with the following Figure 1 When read together, the above and other features of the present application will be more fully described. It is understood that these drawings only depict several implementations of the present application and should not be considered as limiting the scope of the present application. By using the drawings, the present application will be more clearly and detailed.
[0043] Figure 1 This is a diagram showing the appearance of the reaction mixture in Example 1 of the present application when the reaction just begins.
[0044] Figure 2 This is a diagram showing the appearance of the reaction mixture at the end of the reaction of Example 1 of the present application.
[0045] Figure 3 These are appearance diagrams of the reaction mixture in Example 9 of the present application when the reaction just begins and when the reaction ends.
[0046] Figure 4 This is an electron microscope image of the seed microspheres obtained in step S1 of Example 1 of the present application.
[0047] Figure 5 This is an electron microscope image of the seed microspheres during the water phase transfer process in step S3 of Example 1 of the present application.
[0048] Figure 6 This is an electron microscope image of the water-phase quantum dots obtained in Example 1 of the present application. DETAILED DESCRIPTION
[0049] The following examples are described to assist the understanding of the present application, and the examples are not and should not be interpreted in any way as limiting the scope of protection of the present application.
[0050] If not otherwise defined, all terms (including technical and scientific terms) in this specification may be defined as commonly understood by those skilled in the art to which the present disclosure belongs. It will be further understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning consistent with their meaning in the context of the present disclosure and the relevant art, and will be interpreted in a non-idealized or overly formal sense unless clearly defined as such in this article.
[0051] As used herein, the term "at least one", when before or after a list of elements, modifies the entire list of elements without modifying the individual elements of the list, and will not be interpreted as limiting "one". "Or" means "and / or". The terms "include" and "comprise", when used in this specification, indicate the presence of the stated features, regions, wholes, steps, operations, elements, and / or components, but do not exclude the presence or addition of one or more other features, regions, wholes, steps, operations, elements, components, and / or their collections. Therefore, the above wording will be understood to mean including the stated elements, but not excluding any other elements. The term "and / or" includes any and all combinations of one or more of the associated listed items. The term "multiple" refers to two or more. The term "connection" refers to direct or indirect connection. It will be understood that when an element such as a layer, film, region, or substrate is referred to as "on" another element, it may be directly on the other element or there may also be an intermediate element. On the contrary, when an element is referred to as "directly on" another element, there is no intermediate element. In order to clearly illustrate the embodiments in the figures, some parts that are not actually related to the description may be omitted. The terms "first", "second", "third", etc. may be used herein to describe and distinguish various elements, components, regions, layers and / or parts, but these elements, components, regions, layers and / or parts should not be limited by these terms.
[0052] In a first aspect of the present application, a method for transferring oily quantum dots into an aqueous phase is provided, the method comprising:
[0053] S1, preparation of seed microspheres containing oily quantum dots encapsulated in amphiphilic polymers by self-assembly;
[0054] S2, dissolving the seed microspheres in an aqueous solution, and adding a regulator to reduce the polarity of the outer surface of the seed microspheres or reduce the polarity of the aqueous solution;
[0055] S3, adding a hydrophilic ligand into S2 to form a reaction mixture, wherein the hydrophilic ligand combines with the oily quantum dots to transfer the oily quantum dots to a water phase, thereby obtaining water phase quantum dots.
[0056] In some embodiments, in step S1, the self-assembly refers to the amphiphilic polymer and the oily quantum dots, through physical action, to form oily quantum dot seed microspheres encapsulated in the amphiphilic polymer (also called amphiphilic polymer shell).
[0057] Further, specifically, the self-assembly refers to mixing an amphiphilic polymer, oily quantum dots, a non-polar solvent, water and an oil-in-water surfactant, emulsifying to form oil-in-water microdroplets, evaporating / volatizing the non-polar solvent (internal phase solvent of the microdroplets), and forming seed microspheres containing multiple oily quantum dots encapsulated in the amphiphilic polymer.
[0058] Furthermore, the mixed solution forming the seed microspheres is centrifuged to remove the supernatant (to remove the oily quantum dots, amphiphilic polymers and other substances that have not formed the seed microspheres), and then washed and purified, and centrifuged again to remove the supernatant to obtain the seed microspheres.
[0059] The steps of preparing seed microspheres in the present application are prior art, and the method steps of forming oily quantum dots wrapped in amphiphilic polymers by self-assembly in the prior art are applicable to the present application. The principle is that after emulsification to form water-in-oil microdroplets, the oily quantum dots are in the inner phase solvent (i.e., non-polar solvent) of the microdroplets, the lipophilic end of the amphiphilic polymer is inward, contacting the periphery of the inner phase solvent, and the hydrophilic end of the amphiphilic polymer is outward, dissolved in the outer phase solvent (i.e., water) of the microdroplets, so that multiple amphiphilic polymers are arranged along the periphery / periphery of the inner phase solvent, wrapping the inner phase solvent; in the process of evaporation / volatilization to remove the non-polar solvent (heating evaporation / normal temperature evaporation / vacuum evaporation), the microdroplets gradually shrink, and finally the amphiphilic polymer shell layer wraps multiple oily quantum dots to form quantum dot microspheres (i.e., seed microspheres of the present application); and the shape of the quantum dot microspheres is kept from dispersing / breaking, mainly because of the physical effect (such as electrostatic adsorption, etc.) between the oily quantum dots and the amphiphilic polymers.
[0060] The dielectric constant of the non-polar solvent is 1.5-10, and the non-polar solvent can evaporate / volatize at a temperature lower than the boiling point of water. The non-polar solvent is a non-polar solvent with a boiling point lower than the boiling point of water, or a non-polar solvent with a low saturated vapor pressure. The non-polar solvent includes: toluene (boiling point 110°C, but its saturated vapor pressure is relatively low, it completely evaporates after being placed at room temperature for about 14 hours, or evaporates rapidly when heated to 60-80°C, or evaporates rapidly under vacuum), chloroform, benzene, ether, carbon disulfide, carbon tetrachloride, triethylamine, n-hexane, cyclohexane, dichloromethane, or at least one of tetrahydrofuran. In addition to the non-polar solvents listed, non-polar solvents that can evaporate at less than 100°C are also applicable to the present application and are within the scope of protection of the present application.
[0061] The HLB value (hydrophilic-hydrophobic balance or water-oil ratio) of the oil-in-water surfactant is 8 to 18. Common oil-in-water surfactants are anionic surfactants or nonionic surfactants. The oil-in-water surfactant includes: sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, dodecyltrimethylammonium chloride, Tween 80, Tween 60, Tween 20, Triton X-100, polyoxyethylene (16) sorbitan monotoluene ester, polyoxyethylene (10) sorbitan monolaurate, polyoxyethylene (20) sorbitan dioleate, polyoxyethylene (18) sorbitan monostearate, polyoxyethylene (3,8) glycerol monolaurate, polyoxyethylene (16) pentaerythritol monotoluene ester, polyoxyethylene (10) sucrose monooleate, alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, polyoxyethylene fatty amine, polyethylene glycol fatty acid ester, sodium oleate, sodium rosinate, C14-18 alkyl sodium sulfate, sodium dodecylbenzene sulfonate, and dialkyl sulfosuccinate. In addition to the listed oil-in-water surfactants, other common oil-in-water surfactants are also suitable for the present application and are within the protection scope of the present application.
[0062] The emulsification is to emulsify the mixed liquid into oil-in-water micro droplets by ultrasound or stirring.
[0063] In some embodiments, the amphiphilic polymer includes a hydrophilic segment and a lipophilic segment, the hydrophilic segment is soluble in water solvent, and the lipophilic segment is soluble in non-polar solvent.
[0064] Furthermore, the hydrophilic segment includes at least one of polymaleic anhydride, maleic anhydride, polytetracarboxylic anhydride, polyacrylic acid, polyethylene glycol acrylic acid, polyethylene imine, polyimide, polyacrylamide, polyvinyl pyrrolidone, polyethylene glycol, polybutylene glycol, polypropylene glycol, polyethylene glycol monomethyl ether, polyvinyl alcohol, polyvinyl ether, and polyoxyethylene; the lipophilic segment includes at least one of C2-C30 aliphatic hydrocarbon groups (alkyl, alkenyl, alkynyl, etc.), polypropylene oxide, polystyrene, polyethylene, polypropylene, polybutadiene, polyisobutylene, polysiloxane, alcohol ester, polymethyl methacrylate, polyamino acid, and polylactic acid.
[0065] The amphiphilic polymer includes: at least one of polymaleic anhydride octadecyl ester, polymaleic anhydride hexadecyl ester, polymaleic anhydride tetradecyl ester, poly(maleic anhydride-styrene), poly(maleic anhydride-ethylene), poly(maleic anhydride-propylene), poly(maleic anhydride-isobutylene), polyacrylic acid-octylamine, poly(ethylene-acrylic acid), polyacrylic acid dodecylamine, polyethyleneimine octadecyl urea, polyimide octadecyl, polypropyleneimine tridodecylamine, polyvinylpyrrolidone hexadecene, polyvinylpyrrolidone dodecyl, polyethylene glycol dodecyl ether, polyethylene glycol octylphenol ether, polyethylene glycol-polylactic acid, polyethylene glycol polyglutamic acid, polyethylene glycol polylysine, polyoxyethylene hexadecylamine, polyoxyethylene octadecyl ether, polyoxyethylene octylphenol ether, and polyoxyethylene n-octyl ether. In addition to the amphiphilic polymers listed, other common amphiphilic polymers with amphiphilicity are also applicable to the present application and are within the scope of protection of the present application.
[0066] In some embodiments, the surface of the oily quantum dots has lipophilic groups.
[0067] Further, the lipophilic group is a lipophilic group on the surface of the quantum dot, or the lipophilic group is a lipophilic group modified on the surface of the quantum dot. Preferably, the lipophilic group is a lipophilic group on the surface of the quantum dot.
[0068] The quantum dots include: at least one of group IIB-VIA quantum dots, group IIIA-VA quantum dots, group IVA-VIA quantum dots, group IVA quantum dots, group IB-IIIA-VIA quantum dots, group IB-IIB-IVA-VIA quantum dots, group VIII-VIA quantum dots, perovskite quantum dots and carbon quantum dots. For example, group IIB-VIA quantum dots include: CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, MgSe, MgS, CdS eS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZn Te, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, MgZnSe, MgZnS, HgZnTeS, CdZnSeS , CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe or combinations thereof. For example, Group IIIA-VA quantum dots include: GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, InZnP, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb or combinations thereof. For example, IVA-VIA group quantum dots include: SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe or a combination thereof. For example, IVA group quantum dots include: Si, Ge, SiC, SiGe or a combination thereof. For example, IB-IIIA-VIA group quantum dots include: CuInSe2, CuInS2, CuInGaSe, CuInGaS or a combination thereof. For example, IB-IIB-IVA-VIA group quantum dots include: CuZnSnSe, CuZnSnS or a combination thereof.For example, the general structural formula of perovskite quantum dots is one of ABX3, A2B2X6, and A3B3X9, wherein A is a monovalent amine organic cation or a monovalent inorganic metal cation (such as CH3NH3. + 、NH2CHNH2+、C(NH2)3 + , Cs + , Li + 、Na + , K + , Rb + , aromatic groups, etc.), B is a divalent inorganic metal cation (such as a divalent cation of a rare earth metal, a divalent cation of an alkaline earth metal, a divalent cation of a transition metal, a divalent cation of a post-transition metal, etc.), and X is a monovalent anion (such as a halogen, etc.). For example, carbon quantum dots are carbon sources such as organic acids, and are carbonized under high temperature conditions such as microwave ovens or heating to form carbon quantum dots with a particle size of about 10 nm. Most carbon quantum dots are mainly composed of amorphous carbon to a crystallized carbon core with a sp 2 Hybridized carbon. These components are usually the core components of quantum dots, and quantum dots usually also include one or more shells that wrap the core. In addition to the quantum dots listed above, other common quantum dots are also applicable to the present application and are within the scope of protection of the present application. At present, the chemical solution growth method is mainly used to synthesize quantum dots, and the quantum dots prepared by the chemical solution growth method, if not modified by additional ligands, are usually oily quantum dots because the surface of the quantum dots has its own lipophilic groups (such as organic acids such as oleic acid, organic amines such as oleylamine, organic phosphorus such as trioctylphosphine, and thiols such as dodecanethiol).
[0069] The component containing the lipophilic group includes: at least one of an organic acid, an organic amine, an organic phosphine, or a thiol. The organic acid includes: at least one of dodecanoic acid, hexadecanoic acid, octadecanoic acid, oleic acid, undecylenic acid, tetradecylenic acid, stearic acid, or benzoic acid. The organic amine includes: at least one of octylamine, oleylamine, dodecylamine, hexadecylamine, and octadecylamine. The organic phosphine includes: at least one of trioctylphosphine, trioctylphosphine oxide, tributylphosphine, and diphenylphosphine. The thiol includes: at least one of octylmercaptan, dodecanethiol, hexadecylmercaptan, octadecylmercaptan, or benzylmercaptan. In addition to the lipophilic groups listed, other common lipophilic groups are also applicable to the present application and are within the scope of protection of the present application.
[0070] When the lipophilic group is a lipophilic group modified on the surface of the quantum dot, the "modification" refers to the quantum dot and the lipophilic group / the component containing the lipophilic group being combined by a force that does not cause a chemical reaction (such as van der Waals force, electrostatic force, intermolecular force, hydrogen bond, etc.), or by a force that causes a chemical reaction (such as a covalent bond, a metallic bond, etc.).
[0071] In some embodiments, in step S2, in the aqueous solution, the concentration of the seed microspheres is 1-30 mg / ml. Preferably, in the aqueous solution, the concentration of the seed microspheres is 2-25 mg / ml. More preferably, in the aqueous solution, the concentration of the seed microspheres is 4-20 mg / ml.
[0072] In some embodiments, the aqueous solution further comprises: a dispersant. Adding a dispersant can improve the dispersibility of the seed microspheres in the aqueous solution, especially when the concentration of the seed microspheres is high. The dispersant is a hydroxyl-based polymer. The dispersant comprises: at least one of Tween 20, Tween 60, Tween 80, polyvinyl alcohol (PVA), and polyvinyl pyrrolidone (PVP). In addition to the dispersants listed, other dispersants that can improve the dispersibility of the seed microspheres in the aqueous solution are also applicable to the present application and are within the scope of protection of the present application.
[0073] In the present application, after the seed microspheres are dissolved in an aqueous solution, a regulator needs to be added to reduce the polarity of the outer surface of the seed microspheres or reduce the polarity of the aqueous solution.
[0074] In the present application, a regulator is added to the aqueous solution containing seed microspheres in order to reduce the polarity of the outer surface of the seed microspheres, or reduce the polarity of the aqueous solution (also known as reducing the cohesive force of the solvent), that is, to reduce the polarity difference between the inside and outside of the amphiphilic polymer shell. The purpose / reason for doing so is: since the amphiphilic polymer shell of the seed microspheres has pores, that is, there are gaps between adjacent amphiphilic polymers, the hydrophilic ligands of the small molecules of the present application can pass through the pores / gaps to enter the inside of the amphiphilic polymer shell and connect with the oily quantum dots; inside the amphiphilic polymer shell, from the oily quantum dots at the periphery to the oily quantum dots at the center, the oily quantum dots gradually transfer from the water phase to the water phase quantum dots. After the quantum dots are successfully transferred to the water phase, their polarity changes, and the oily quantum dots that have not yet transferred to the water phase / the quantum dots that have not completed the transfer to the water phase will repel the water phase quantum dots that have successfully transferred to the water phase. If a regulator is not used to reduce the polarity difference inside and outside the amphiphilic polymer shell, the polarity difference inside and outside the amphiphilic polymer shell is very large, and the seed microspheres cannot successfully spit out / discharge the water phase quantum dots that have successfully transferred to the water phase. The regulator is used to reduce the polarity difference inside and outside the amphiphilic polymer shell. Since the oily quantum dots in the peripheral position complete the transfer to the water phase first, the repulsive force of other oil phase quantum dots on the water phase quantum dots is directed to the outside of the shell. Since the polarity difference inside and outside the amphiphilic polymer shell is reduced, the repulsive force is greater than the polarity difference, and the pores of the amphiphilic polymer shell (i.e., there is a gap between adjacent amphiphilic polymers) become larger, and the water phase quantum dots are spit out / discharged into the aqueous solution outside the seed microspheres. After the water phase quantum dots are discharged, the repulsive force becomes smaller, and the pores of the amphiphilic polymer shell are reduced again; continue this process, and discharge the water phase quantum dots one after another. In the embodiment of the present application, it is also detected that the particle size of the seed microspheres is getting smaller, and the reaction mixture gradually changes from turbid to clear.
[0075] Prior art 1 is to directly transfer oily quantum dots to water phase in aqueous solution. The quantum dots are directly immersed in water, that is, the quantum dots are directly in contact with water, and the quantum dots are easily affected by water / oxygen, which reduces the fluorescence efficiency of the quantum dots and even quenches a large number of quantum dots. At the same time, oily quantum dots are insoluble in water, similar to the interfacial reaction, and the yield of oily quantum dots to water phase is low.
[0076] Prior art 2 uses oily quantum dots, non-polar solvents, water and water-in-oil surfactants to emulsify into water-in-oil microdroplets, and then adds hydrophilic ligands. The oily quantum dots react with the hydrophilic ligands at the interface of the microdroplets. The fluorescence efficiency of the water-phase quantum dots is improved compared to technology 1, but the oily quantum dots at the interface are still in contact with water. At the same time, the efficiency of the interfacial reaction is not high. Only the oily quantum dots at the interface can be transferred to the water phase. The yield of the transfer to the water phase is low, and due to the low efficiency, the time for the oily quantum dots to transfer to the water phase is long.
[0077] Prior art 3 uses oily quantum dots, chloroform, and amphiphilic ligands soluble in chloroform (such as thiol PEG, etc.), the amphiphilic ligands react with the oily quantum dots, the oily groups of the amphiphilic ligands are consumed (such as the thiol groups of thiol PEG are consumed), and the quantum dots are transferred to the water phase. After the quantum dots are transferred to the water phase, since the solvent is chloroform, the water phase quantum dots will precipitate, so it is necessary to continuously add polar solvents such as ethanol during the reaction process. The amount of polar solvent added / the speed of addition needs to match the speed of the reaction between the amphiphilic ligand and the oily quantum dots, so that the quantum dots that are being transferred to the water phase will not precipitate, be in a dispersed state, and transfer to the water phase will be more thorough; if the quantum dots are precipitated, they will not be able to contact the amphiphilic ligands, and the transfer to the water phase will fail. It can be seen from the principle description that it is difficult to control the amount of polar solvent added to match the reaction speed. In actual synthesis experiments / production, the failure rate is very high (about half the failure rate), it is difficult to mass produce, and the overall yield of the transfer to the water phase is low.
[0078] In the present application, since the inside of the seed microspheres are all hydrophobic substances, although the amphiphilic polymer shell has pores, due to the repulsive effect of different polarities, it is difficult for water to penetrate into the inside of the seed microspheres during the reaction process, and after the water phase quantum dots that have successfully transferred phases are discharged outside the seed microspheres, since the surface of the water phase quantum dots is combined with a large number of hydrophilic ligands, its strong hydrophilicity forms a hydration layer protection, and the quantum dots rarely come into contact with water, and the fluorescence efficiency of the quantum dots is significantly improved. At the same time, the coordination groups of the hydrophilic ligands have chelating forces with the quantum dots in the amphiphilic polymer shell, and the hydrophilic ligands have a small molecular weight and can pass through the pores of the amphiphilic polymer shell, so that the hydrophilic ligands enter the inside of the amphiphilic polymer shell, and continuously react and connect with the oily quantum dots, and the quantum dots transfer to the water phase with a high yield.
[0079] In addition, in the process of quantum dots being transferred to the water phase of the present application, only quantum dots that are completely transferred to the water phase will be expelled from the seed microspheres, and quantum dots that are not completely transferred to the water phase will not be expelled from the seed microspheres due to the insufficient repulsive force. Therefore, the technical solution of the present application also plays a role in distinguishing whether the quantum dots are successfully transferred to the water phase. In the prior art, it is difficult to distinguish and screen quantum dots that are completely transferred to the water phase from quantum dots that are partially / incompletely transferred to the water phase.
[0080] In some embodiments, in step S2, a regulator is added so that the absolute value of the difference in polarity parameters inside and outside the amphiphilic polymer shell is less than the absolute value of the difference in polarity parameters between the water phase quantum dots and the oil phase quantum dots. Preferably, the regulator is added so that the absolute value of the difference in polarity parameters inside and outside the amphiphilic polymer shell is 5-7.5. Preferably, the regulator is added so that the absolute value of the difference in polarity parameters inside and outside the amphiphilic polymer shell is 6-7.
[0081] The applicant has found that the outer shell of the amphiphilic polymer of the present application is water, and the inner shell is oily quantum dots, wherein the polarity parameter of water is 10.4, and the polarity parameter of the oily quantum dots in the shell is -0.2 (with cyclohexane as the boundary). If no regulator is added, the absolute value of the difference in polarity parameters inside and outside the amphiphilic polymer shell is 10.6. The polarity parameter of the water phase quantum dots of the present application is greater than 8 (8-9.6). Therefore, when no regulator is added, the repulsive force between the quantum dots is less than the polarity difference force inside and outside the amphiphilic polymer shell, and the water phase quantum dots cannot be discharged from the inside of the seed microsphere. When the absolute value of the difference in polarity parameters inside and outside the amphiphilic polymer shell is less than the absolute value of the difference in polarity parameters between the water phase quantum dots and the oil phase quantum dots, the water phase quantum dots can be discharged from the inside of the seed microsphere. The applicant has found through repeated verification that when the absolute value of the difference in polarity parameters inside and outside the amphiphilic polymer shell is 5-7.5, the oily quantum dots can be successfully transferred to the water phase under the protection of the amphiphilic polymer shell; if the absolute value of the difference is greater than 7.5, the repulsive force of other quantum dots on the water phase quantum dots is less than the polarity difference force of the amphiphilic polymer shell, and the water phase quantum dots cannot be discharged outside the amphiphilic polymer; if the absolute value of the difference is less than 5, the seed microspheres are easy to settle, or the seed microspheres are easy to collapse in the process of discharging the water phase quantum dots.
[0082] Furthermore, the regulator includes at least one of an esterification catalyst, water-soluble aldehydes, water-soluble glycerol ethers, salts, and polar solvents.
[0083] The esterification catalyst reacts with the hydrophilic group of the hydrophilic segment of the amphiphilic polymer to generate an amine-reactive ester, which reduces the polarity of the hydrophilic segment (i.e., reduces the polarity of the outer surface of the seed microsphere), so that the absolute value of the difference in polarity parameters inside and outside the amphiphilic polymer shell is between 5-7.5. The water-soluble aldehydes and water-soluble glycerol ethers react with the hydrophilic groups of the hydrophilic segment of the amphiphilic polymer, consume the hydrophilic groups, and introduce non-polar groups, which reduces the polarity of the hydrophilic segment (i.e., reduces the polarity of the outer surface of the seed microsphere), so that the absolute value of the difference in polarity parameters inside and outside the amphiphilic polymer shell is between 5-7.5. The salts and polar solvents reduce the polarity of the aqueous solution (reduce the cohesion of the aqueous solution), so that the absolute value of the difference in polarity parameters inside and outside the amphiphilic polymer shell is between 5-7.5. In addition to the listed regulators, other regulators that can make the absolute value of the difference in polarity parameters between the inner and outer shells of the amphiphilic polymer layer be 5-7.5 are also applicable to the present application and are within the protection scope of the present application.
[0084] Preferably, when a regulator for reducing the polarity of the outer surface of the seed microspheres and a regulator for reducing the polarity of the aqueous solution are added simultaneously, the reaction time of the reaction mixture in step S3 can be reduced.
[0085] Furthermore, the esterification catalyst includes: at least one of a water-soluble carbodiimide salt and a water-soluble imide salt. In the aqueous solution of step S2, the esterification catalyst is added to the seed microspheres in a mass ratio of 1:(2-10).
[0086] Furthermore, the esterification catalyst includes at least one of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC), 2-(7-azabenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate (HATU), N-hydroxysuccinimide (HoBT), N-hydroxysuccinimide (NHS), and N-hydroxysulfosuccinimide (Sulfo-NHS).
[0087] Furthermore, in the aqueous solution of step S2, the water-soluble aldehydes are added to the seed microspheres in a mass ratio of 1:(2-10), and the water-soluble aldehydes include at least one of glutaraldehyde, acetone aldehyde, acetaldehyde, succinaldehyde, and adipaldehyde.
[0088] Furthermore, in the aqueous solution of step S2, the mass ratio of the water-soluble glyceryl ether to the seed microspheres is 1:(2-10); the water-soluble glyceryl ether includes at least one of diglycidyl ether, allyl glycidyl ether, glycerol triglycidyl ether, and butanediol diglycidyl ether.
[0089] Furthermore, in the aqueous solution of step S2, the mass ratio of the salt added is 0.3-0.5 mg / ml; the salt includes: at least one of sodium chloride, potassium chloride, sodium bicarbonate, sodium carbonate, and calcium chloride.
[0090] Furthermore, the dielectric constant of the polar solvent is ≥18, and the mass ratio of the polar solvent to water added to the aqueous solution in step S2 is 1:(10-100). The polar solvent includes at least one of methanol, ethanol, ethylene glycol, diformamide, butanone, acetone, n-propanol, isopropanol, n-butanol, DMSO (dimethyl sulfoxide), tetrahydrofuran, and pyridine.
[0091] In some embodiments, in step S3, the hydrophilic ligand includes: a coordination group and a hydrophilic group, the coordination group can be connected to the surface of the oily quantum dots, and the hydrophilic group provides hydrophilicity to the quantum dots.
[0092] Further, the molecular weight of the hydrophilic ligand is 50-400. Preferably, the molecular weight of the hydrophilic ligand is 50-300.
[0093] Furthermore, the coordination group includes at least one of thiol, phosphate, amide, carboxyl and amino.
[0094] Furthermore, the hydrophilic group includes at least one of a hydroxyl group, a carboxyl group, an amino group, an imino group, a phosphate group, a quaternary ammonium group, an amide group, and an aldehyde group.
[0095] Furthermore, the hydrophilic components containing hydrophilic groups include: acids such as propionic acid, acetic acid, succinic acid, hexanoic acid and their derivatives, amines such as ethylamine, propylamine, butylamine, pentylamine, hexylamine, heptylamine and their derivatives, alcohols such as ethanol, ethylene glycol, propylene glycol, propanol, butanediol, vinyl alcohol and their derivatives, acid anhydrides and their derivatives, and at least one of amino acids.
[0096] The hydrophilic ligand includes at least one of mercaptopropionic acid, mercaptoacetic acid, mercaptosuccinic acid, mercaptohexanoic acid, mercaptoethylamine, mercaptopropylamine, mercaptobutylamine, mercaptopentylamine, mercaptohexylamine, mercaptoheptylamine, mercaptoethanol, mercaptoethylene glycol, mercaptopropylene glycol, mercaptopropanol, mercaptobutylene glycol, mercaptovinyl alcohol, amino acids, isomeric alcohol ether phosphates, hydroxypropyl phosphates, ethyl phosphate, diethyl phosphate, triethyl phosphate, and ethylene glycol phosphate. In addition to the hydrophilic ligands listed above, hydrophilic ligands with a molecular weight of 50-400 commonly used in the prior art are also applicable to the present application and are within the scope of protection of the present application.
[0097] The hydrophilic ligand of the present application is connected to the oily quantum dots to transfer the oily quantum dots to the water phase, and the hydrophilic ligand is grafted on the outer surface of the oily quantum dots, or the hydrophilic ligand replaces the lipophilic group on the surface of the oily quantum dots / the component containing the lipophilic group. Preferably, the hydrophilic ligand of the present application is connected to the oily quantum dots to transfer the oily quantum dots to the water phase, and the hydrophilic ligand replaces the lipophilic group on the surface of the oily quantum dots / the component containing the lipophilic group.
[0098] In some embodiments, the mass ratio of the oily quantum dots to the hydrophilic ligands added to the reaction mixture is 1:(0.1-0.3.
[0099] In some embodiments, the reaction mixture is reacted at 10-50° C. and a stirring speed of 100-1000 rpm for 3-20 hours to obtain water-phase quantum dots.
[0100] In some embodiments, the reaction mixture containing water-phase quantum dots is purified to obtain water-phase quantum dots.
[0101] Furthermore, the reaction mixture containing the water-phase quantum dots is centrifuged to remove the precipitate, or filtered to remove the seed microspheres after the water-phase quantum dots are discharged, and then a purification solvent is added to precipitate the water-phase quantum dots and remove excess unreacted products (such as excess hydrophilic ligands, regulators, etc.) to obtain water-phase quantum dots.
[0102] The purification solvent includes at least one of saturated salts such as DMSO, saturated sodium chloride, saturated potassium chloride, saturated sodium bicarbonate, saturated sodium carbonate, and saturated calcium chloride.
[0103] In some embodiments, the luminescence quantum yield of the water-phase quantum dots is ≥88%.
[0104] In some embodiments, the yield of the oily quantum dot-water-phase conversion is ≥85%.
[0105] In a second aspect of the present application, a water-phase quantum dot is provided, wherein the water-phase quantum dot is obtained by the above-mentioned method of converting the oil-phase quantum dot to the water phase.
[0106] In some embodiments, the luminescence quantum yield of the water-phase quantum dots is ≥88%.
[0107] The present invention will be further described in detail below in conjunction with specific embodiments and comparative examples, but the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to different requirements of specific use, and the unspecified conditions are conventional conditions in the industry.
[0108] Embodiment 1:
[0109] S1, preparation of seed microspheres: 400 mg of CdSe / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface), 200 mg of PMAO (polymaleic anhydride octadecyl ester) and 10 ml of chloroform were mixed, and mixed evenly at room temperature 25°C and 400W ultrasound for 10 min. Then added to 50 ml of aqueous solution containing SDS (sodium dodecyl sulfate) (the concentration of SDS is 4 mg / ml), stirred at 500 rpm for 10 min at room temperature 25°C. Then heated to 70°C, maintained for 2 hours, and chloroform was evaporated. Centrifuged to remove the supernatant, then washed with water once, and centrifuged again to remove the supernatant to obtain seed microspheres.
[0110] S2, reduce polarity difference: dissolve the above seed microspheres in 70 ml of water, then add 100 mg of EDC (1-ethyl-(3-dimethylaminopropyl)carbodiimide) and 200 mg of NHS (N-hydroxysuccinimide), and stir at 400 rpm for 30 min at room temperature 25°C.
[0111] S3, transfer to aqueous phase: add 500 mg of thioglycolic acid to S2, stir at room temperature 25°C and 400 rpm for 16 h, the reaction mixture gradually changes from turbid to clear. The appearance of the reaction mixture at the beginning of the reaction is as shown in the figure Figure 1 As shown, the appearance of the reaction mixture at the end of the reaction is as shown in Figure 2Centrifuge to remove the precipitate (seed microspheres after the quantum dots are discharged); add 2 ml of saturated sodium chloride to precipitate the water-phase quantum dots to obtain the water-phase quantum dots.
[0112] The seed microspheres obtained in step S1, the seed microspheres in the process of transferring to the aqueous phase in step S3, and the aqueous phase quantum dots are photographed using a field emission transmission electron microscope (TEM), respectively, as shown in FIG. Figure 4 , Figure 5 , Figure 6 shown.
[0113] The reaction mixture gradually changed from turbid to clear, indicating that the oily quantum dots have been converted into water-phase quantum dots. Figure 4 It can be seen that the average particle size of the seed microspheres is about 120nm. Figure 6 The particle size of water-phase quantum dots is about 12nm. Figure 5 It shows that the seed microspheres are expelling the aqueous phase quantum dots after the successful transfer to the aqueous phase.
[0114] Embodiment 2:
[0115] S1, preparation of seed microspheres: 400 mg of CdSe / ZnSeS / ZnS red light quantum dots (with oleic acid and thiol on the surface), 200 mg of poly(maleic anhydride-styrene) and 10 ml of n-hexane were mixed, and mixed evenly at room temperature 25°C and 400W ultrasound for 10 min. Then added to 50 ml of aqueous solution containing Tween 80 (the concentration of Tween 80 is 4 mg / ml), stirred at 500 rpm for 10 min at room temperature 25°C. Then heated to 72°C, maintained for 2 hours, and the n-hexane was evaporated. Centrifuged to remove the supernatant, then washed with water once, and centrifuged again to remove the supernatant to obtain seed microspheres.
[0116] S2, reduce polarity difference: dissolve the above seed microspheres in 35 ml of aqueous solution containing polyvinyl pyrrolidone (polyvinyl pyrrolidone concentration is 1 mg / ml), then add 100 mg of HoBT (N-hydroxysuccinimide), and stir at room temperature 25°C and 400 rpm for 30 min.
[0117] S3, transfer to water phase: add 500 mg of mercaptoethylamine to S2, stir at room temperature 25°C and 400 rpm for 16 hours, the reaction mixture gradually changes from turbid to clear. Centrifuge to remove the precipitate; add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots, and obtain the water phase quantum dots.
[0118] Embodiment 3:
[0119] S1, preparation of seed microspheres: 400 mg of CdSe / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface), 200 mg of poly(ethylene-acrylic acid) and 10 ml of toluene were mixed, and mixed evenly at room temperature 25°C and 400W ultrasound for 10 min. Then added to 50 ml of aqueous solution containing Tween 20 (the concentration of Tween 20 is 4 mg / ml), stirred at 500 rpm for 10 min at room temperature 25°C. Then heated to 70°C, maintained for 2 hours, and toluene was evaporated. Centrifuged to remove the supernatant, then washed with water once, and centrifuged again to remove the supernatant to obtain seed microspheres.
[0120] S2, reduce polarity difference: dissolve the above seed microspheres in 50 ml of water, then add 100 mg of EDC (1-ethyl-(3-dimethylaminopropyl)carbodiimide) and 200 mg of Sulfo-NHS (N-hydroxysulfosuccinimide), and stir at 400 rpm for 30 min at room temperature 25°C.
[0121] S3, transfer to water phase: add 500 mg of mercaptoethanol to S2, stir at room temperature 25°C and 400 rpm for 16 hours, and the reaction mixture gradually changes from turbid to clear. Centrifuge to remove the precipitate; add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots to obtain water phase quantum dots.
[0122] Embodiment 4:
[0123] S1, preparation of seed microspheres: 400 mg of CdSe / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface), 200 mg of polyethyleneimine octadecyl urea and 10 ml of chloroform were mixed, and mixed evenly at room temperature of 25°C and 400W ultrasound for 10 min. Then add it to 50 ml of aqueous solution containing SDS (sodium dodecyl sulfate) (the concentration of SDS is 4 mg / ml), and stir at 500 rpm for 10 min at room temperature of 25°C. Then heat it to 70°C, keep it for 2 hours, and evaporate the chloroform. Centrifuge to remove the supernatant, then wash it with water once, and centrifuge it again to remove the supernatant to obtain seed microspheres.
[0124] S2, reducing polarity differences: dissolve the above seed microspheres in 50 ml of water, then add 100 mg of glutaraldehyde, and stir at 400 rpm for 30 min at room temperature 25°C.
[0125] S3, transfer to water phase: add 500 mg of mercaptopropionic acid to S2, stir at room temperature 25°C and 400 rpm for 16 hours, and the reaction mixture gradually changes from turbid to clear. Centrifuge to remove the precipitate; add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots to obtain water phase quantum dots.
[0126] Embodiment 5:
[0127] S1, preparation of seed microspheres: 400 mg of CdSe / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface), 200 mg of polyethyleneimine octadecyl urea and 10 ml of chloroform were mixed, and mixed evenly at room temperature of 25°C and 400W ultrasound for 10 min. Then add it to 50 ml of aqueous solution containing SDS (sodium dodecyl sulfate) (the concentration of SDS is 4 mg / ml), and stir at 500 rpm for 10 min at room temperature of 25°C. Then heat it to 70°C, keep it for 2 hours, and evaporate the chloroform. Centrifuge to remove the supernatant, then wash it with water once, and centrifuge it again to remove the supernatant to obtain seed microspheres.
[0128] S2, reducing polarity differences: dissolve the above seed microspheres in 50 ml of water, then add 100 mg of propenyl glycidyl ether, and stir at 400 rpm for 30 min at room temperature 25°C.
[0129] S3, transfer to water phase: add 500 mg of mercaptopropylamine to S2, stir at room temperature 25°C and 400 rpm for 16 hours, and the reaction mixture gradually changes from turbid to clear. Centrifuge to remove the precipitate; add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots to obtain water phase quantum dots.
[0130] Embodiment 6:
[0131] S1, preparation of seed microspheres: 400 mg of CdSe / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface), 200 mg of polymaleic anhydride octadecyl ester and 10 ml of chloroform were mixed, and mixed evenly at room temperature of 25°C and 400W ultrasound for 10 min. Then added to 50 ml of aqueous solution containing SDS (sodium dodecyl sulfate) (the concentration of SDS is 4 mg / ml), stirred at 500 rpm for 10 min at room temperature of 25°C. Then heated to 70°C, maintained for 2 hours, and chloroform was evaporated. Centrifuged to remove the supernatant, then washed with water once, and centrifuged again to remove the supernatant to obtain seed microspheres.
[0132] S2, reduce polarity difference: dissolve the above seed microspheres in 50 ml of water, add 2.5 ml of ethanol, then add 100 mg of EDC (1-ethyl-(3-dimethylaminopropyl)carbodiimide) and 200 mg of NHS (N-hydroxysuccinimide), and stir at 400 rpm for 30 min at room temperature 25°C.
[0133] S3, transfer to water phase: add 500 mg of mercaptopropanol to S2, stir at room temperature 25°C and 400 rpm for 6 hours, and the reaction mixture gradually changes from turbid to clear. Centrifuge to remove the precipitate; add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots to obtain water phase quantum dots.
[0134] Embodiment 7:
[0135] S1, preparation of seed microspheres: 400 mg of CdSe / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface), 200 mg of polymaleic anhydride octadecyl ester and 10 ml of chloroform were mixed, and mixed evenly at room temperature of 25°C and 400W ultrasound for 10 min. Then added to 50 ml of aqueous solution containing SDS (sodium dodecyl sulfate) (the concentration of SDS is 4 mg / ml), stirred at 500 rpm for 10 min at room temperature of 25°C. Then heated to 70°C, maintained for 2 hours, and chloroform was evaporated. Centrifuged to remove the supernatant, then washed with water once, and centrifuged again to remove the supernatant to obtain seed microspheres.
[0136] S2, reduce polarity difference: dissolve the above seed microspheres in 50 ml of water, add 0.3 ml of saturated sodium chloride, then add 100 mg of EDC (1-ethyl-(3-dimethylaminopropyl)carbodiimide) and 200 mg of NHS (N-hydroxysuccinimide), and stir at 400 rpm for 30 min at room temperature 25°C.
[0137] S3, transfer to water phase: add 500 mg of mercaptopropanol to S2, stir at room temperature 25°C and 400 rpm for 6 hours, and the reaction mixture gradually changes from turbid to clear. Centrifuge to remove the precipitate; add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots to obtain water phase quantum dots.
[0138] Embodiment 8:
[0139] S1, preparation of seed microspheres: 400 mg of InP / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface), 200 mg of PMAO (polymaleic anhydride octadecyl ester) and 10 ml of chloroform were mixed, and mixed evenly at room temperature 25°C and 400W ultrasound for 10 min. Then added to 50 ml of aqueous solution containing SDS (sodium dodecyl sulfate) (the concentration of SDS is 4 mg / ml), stirred at 500 rpm for 10 min at room temperature 25°C. Then heated to 70°C, maintained for 2 hours, and chloroform was evaporated. Centrifuged to remove the supernatant, then washed with water once, and centrifuged again to remove the supernatant to obtain seed microspheres.
[0140] S2, reduce polarity difference: dissolve the above seed microspheres in 70 ml of water, then add 100 mg of EDC (1-ethyl-(3-dimethylaminopropyl)carbodiimide) and 200 mg of NHS (N-hydroxysuccinimide), and stir at 400 rpm for 30 min at room temperature 25°C.
[0141] S3, transfer to water phase: add 500 mg of thioglycolic acid to S2, stir at room temperature 25°C and 400 rpm for 16 hours, the reaction mixture gradually changes from turbid to clear. Centrifuge to remove the precipitate; add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots, and obtain the water phase quantum dots.
[0142] Embodiment 9:
[0143] S1, preparation of seed microspheres: 400 mg of InP / ZnSeS / ZnS red light quantum dots (with oleic acid and thiol on the surface), 200 mg of poly(maleic anhydride-styrene) and 10 ml of n-hexane were mixed, and mixed evenly at room temperature 25°C and 400W ultrasound for 10 min. Then added to 50 ml of aqueous solution containing Tween 80 (the concentration of Tween 80 is 4 mg / ml), stirred at 500 rpm for 10 min at room temperature 25°C. Then heated to 72°C, maintained for 2 hours, and the n-hexane was evaporated. Centrifuged to remove the supernatant, then washed with water once, and centrifuged again to remove the supernatant to obtain seed microspheres.
[0144] S2, reduce polarity difference: dissolve the above seed microspheres in 35 ml of aqueous solution containing polyvinyl pyrrolidone (polyvinyl pyrrolidone concentration is 1 mg / ml), then add 100 mg of HoBT (N-hydroxysuccinimide), and stir at room temperature 25°C and 400 rpm for 30 min.
[0145] S3, transfer to aqueous phase: add 500 mg of mercaptoethylamine to S2, stir at room temperature 25°C and 400 rpm for 16 h, the reaction mixture gradually changes from turbid to clear. The appearance of the reaction mixture at the beginning and end of the reaction is shown in the figure below: Figure 3 Centrifuge to remove the precipitate; add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots to obtain the water phase quantum dots.
[0146] Embodiment 10:
[0147] S1, preparation of seed microspheres: 400 mg of InP / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface), 200 mg of poly(ethylene-acrylic acid) and 10 ml of toluene were mixed, and mixed evenly at room temperature of 25°C and 400W ultrasound for 10 min. Then added to 50 ml of aqueous solution containing Tween 20 (the concentration of Tween 20 is 4 mg / ml), stirred at 500 rpm for 10 min at room temperature of 25°C. Then heated to 70°C, maintained for 2 hours, and toluene was evaporated. Centrifuged to remove the supernatant, then washed with water once, and centrifuged again to remove the supernatant to obtain seed microspheres.
[0148] S2, reduce polarity difference: dissolve the above seed microspheres in 50 ml of water, then add 100 mg of EDC (1-ethyl-(3-dimethylaminopropyl)carbodiimide) and 200 mg of Sulfo-NHS (N-hydroxysulfosuccinimide), and stir at 400 rpm for 30 min at room temperature 25°C.
[0149] S3, transfer to water phase: add 500 mg of mercaptoethanol to S2, stir at room temperature 25°C and 400 rpm for 16 hours, and the reaction mixture gradually changes from turbid to clear. Centrifuge to remove the precipitate; add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots to obtain water phase quantum dots.
[0150] Embodiment 11:
[0151] S1, preparation of seed microspheres: 400 mg of InP / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface), 200 mg of polyethyleneimine octadecyl urea and 10 ml of chloroform were mixed, and mixed evenly at room temperature of 25°C and 400W ultrasound for 10 min. Then add it to 50 ml of aqueous solution containing SDS (sodium dodecyl sulfate) (the concentration of SDS is 4 mg / ml), and stir at 500 rpm for 10 min at room temperature of 25°C. Then heat it to 70°C, keep it for 2 hours, and evaporate the chloroform. Centrifuge to remove the supernatant, then wash it with water once, and centrifuge it again to remove the supernatant to obtain seed microspheres.
[0152] S2, reducing polarity differences: dissolve the above seed microspheres in 50 ml of water, then add 100 mg of glutaraldehyde, and stir at 400 rpm for 30 min at room temperature 25°C.
[0153] S3, transfer to water phase: add 500 mg of mercaptopropionic acid to S2, stir at room temperature 25°C and 400 rpm for 16 hours, and the reaction mixture gradually changes from turbid to clear. Centrifuge to remove the precipitate; add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots to obtain water phase quantum dots.
[0154] Embodiment 12:
[0155] S1, preparation of seed microspheres: 400 mg of InP / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface), 200 mg of polyethyleneimine octadecyl urea and 10 ml of chloroform were mixed, and mixed evenly at room temperature of 25°C and 400W ultrasound for 10 min. Then add it to 50 ml of aqueous solution containing SDS (sodium dodecyl sulfate) (the concentration of SDS is 4 mg / ml), and stir at 500 rpm for 10 min at room temperature of 25°C. Then heat it to 70°C, keep it for 2 hours, and evaporate the chloroform. Centrifuge to remove the supernatant, then wash it with water once, and centrifuge it again to remove the supernatant to obtain seed microspheres.
[0156] S2, reducing polarity differences: dissolve the above seed microspheres in 50 ml of water, then add 100 mg of propenyl glycidyl ether, and stir at 400 rpm for 30 min at room temperature 25°C.
[0157] S3, transfer to water phase: add 500 mg of mercaptopropylamine to S2, stir at room temperature 25°C and 400 rpm for 16 hours, and the reaction mixture gradually changes from turbid to clear. Centrifuge to remove the precipitate; add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots to obtain water phase quantum dots.
[0158] Embodiment 13:
[0159] S1, preparation of seed microspheres: 400 mg of InP / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface), 200 mg of polymaleic anhydride octadecyl ester and 10 ml of chloroform were mixed, and mixed evenly at room temperature 25°C and 400W ultrasound for 10 min. Then added to 50 ml of aqueous solution containing SDS (sodium dodecyl sulfate) (the concentration of SDS is 4 mg / ml), stirred at 500 rpm for 10 min at room temperature 25°C. Then heated to 70°C, maintained for 2 hours, and chloroform was evaporated. Centrifuged to remove the supernatant, then washed with water once, and centrifuged again to remove the supernatant to obtain seed microspheres.
[0160] S2, reduce polarity difference: dissolve the above seed microspheres in 50 ml of water, add 2.5 ml of ethanol, then add 100 mg of EDC (1-ethyl-(3-dimethylaminopropyl)carbodiimide) and 200 mg of NHS (N-hydroxysuccinimide), and stir at 400 rpm for 30 min at room temperature 25°C.
[0161] S3, transfer to water phase: add 500 mg of mercaptopropanol to S2, stir at room temperature 25°C and 400 rpm for 6 hours, and the reaction mixture gradually changes from turbid to clear. Centrifuge to remove the precipitate; add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots to obtain water phase quantum dots.
[0162] Embodiment 14:
[0163] S1, preparation of seed microspheres: 400 mg of InP / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface), 200 mg of polymaleic anhydride octadecyl ester and 10 ml of chloroform were mixed, and mixed evenly at room temperature 25°C and 400W ultrasound for 10 min. Then added to 50 ml of aqueous solution containing SDS (sodium dodecyl sulfate) (the concentration of SDS is 4 mg / ml), stirred at 500 rpm for 10 min at room temperature 25°C. Then heated to 70°C, maintained for 2 hours, and chloroform was evaporated. Centrifuged to remove the supernatant, then washed with water once, and centrifuged again to remove the supernatant to obtain seed microspheres.
[0164] S2, reduce polarity difference: dissolve the above seed microspheres in 50 ml of water, add 0.3 ml of saturated sodium chloride, then add 100 mg of EDC (1-ethyl-(3-dimethylaminopropyl)carbodiimide) and 200 mg of NHS (N-hydroxysuccinimide), and stir at 400 rpm for 30 min at room temperature 25°C.
[0165] S3, transfer to water phase: add 500 mg of mercaptopropanol to S2, stir at room temperature 25°C and 400 rpm for 6 hours, and the reaction mixture gradually changes from turbid to clear. Centrifuge to remove the precipitate; add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots to obtain water phase quantum dots.
[0166] Comparative Example 1:
[0167] Preparation of seed microspheres: Mix 400 mg of CdSe / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface), 200 mg of PMAO (polymaleic anhydride octadecyl ester) and 10 ml of chloroform, and mix them evenly at room temperature 25°C and 400W ultrasound for 10 minutes. Then add it to 50 ml of an aqueous solution containing SDS (sodium dodecyl sulfate) (the concentration of SDS is 4 mg / ml), and stir it at 500 rpm for 10 minutes at room temperature 25°C. Then heat it to 70°C, keep it for 2 hours, and evaporate the chloroform. Centrifuge to remove the supernatant, then wash it with water once, and centrifuge it again to remove the supernatant to obtain seed microspheres.
[0168] Transfer to water phase: Dissolve the seed microspheres in 50 ml of water, add 500 mg of thioglycolic acid, stir at 400 rpm for 16 h at room temperature 25 °C, and the reaction mixture is always turbid. Centrifuge to remove the precipitate; add 2 ml of saturated sodium chloride, and almost no water phase quantum dot precipitation is obtained.
[0169] Comparative Example 2:
[0170] Preparation of seed microspheres: Mix 400 mg of InP / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface), 200 mg of PMAO (polymaleic anhydride octadecyl ester) and 10 ml of chloroform, and mix them evenly at room temperature 25°C and 400W ultrasound for 10 minutes. Then add it to 50 ml of an aqueous solution containing SDS (sodium dodecyl sulfate) (the concentration of SDS is 4 mg / ml), and stir it at 500 rpm for 10 minutes at room temperature 25°C. Then heat it to 70°C, keep it for 2 hours, and evaporate the chloroform. Centrifuge to remove the supernatant, then wash it with water once, and centrifuge it again to remove the supernatant to obtain seed microspheres.
[0171] Transfer to water phase: Dissolve the seed microspheres in 50 ml of water, add 500 mg of thioglycolic acid, stir at 400 rpm for 16 h at room temperature 25 °C, and the reaction mixture is always turbid. Centrifuge to remove the precipitate; add 2 ml of saturated sodium chloride, and almost no water phase quantum dot precipitation is obtained.
[0172] Comparative Example 3:
[0173] Add 500 mg of thioglycolic acid to 50 ml of water, stir at room temperature 25°C and 400 rpm for 10 min to mix evenly. Keep stirring at room temperature 25°C and 400 rpm, add 400 mg of CdSe / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface) dropwise, and continue stirring for 2 hours. Centrifuge to remove the supernatant (solvent, excess thioglycolic acid), then wash once with water, add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots, and obtain water phase quantum dots.
[0174] Comparative Example 4:
[0175] Add 500 mg of thioglycolic acid to 50 ml of water, stir at room temperature 25°C and 400 rpm for 10 min to mix evenly. Keep stirring at room temperature 25°C and 400 rpm, add 400 mg of InP / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface) dropwise, and continue stirring for 2 hours. Centrifuge to remove the supernatant, then wash once with water, add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots, and obtain water phase quantum dots.
[0176] Comparative Example 5:
[0177] Add 500 mg of thioglycolic acid to 50 ml of water, stir at room temperature 25°C and 400 rpm for 10 min to mix evenly. Keep stirring at room temperature 25°C and 400 rpm, add 400 mg of CdSe / ZnSeS / ZnS red light quantum dots (with oleic acid and thiol on the surface) dropwise, and continue stirring for 2 hours. Centrifuge to remove the supernatant (solvent, excess thioglycolic acid), then wash once with water, add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots, and obtain water phase quantum dots.
[0178] Comparative Example 6:
[0179] Add 500 mg of thioglycolic acid to 50 ml of water, stir at room temperature 25°C and 400 rpm for 10 min to mix evenly. Keep stirring at room temperature 25°C and 400 rpm, add 400 mg of InP / ZnSeS / ZnS red light quantum dots (with oleic acid and thiol on the surface) dropwise, and continue stirring for 2 hours. Centrifuge to remove the supernatant, then wash once with water, add 2 ml of saturated sodium chloride to precipitate the water phase quantum dots, and obtain water phase quantum dots.
[0180] Comparative Example 7:
[0181] Preparation of oil phase solution: 400 mg of CdSe / ZnSeS / ZnS green light quantum dots (with oleic acid and oleylamine on the surface) were mixed with 10 ml of chloroform, and stirred at 400 rpm for 10 min at room temperature of 25°C to mix evenly. Preparation of water phase solution: 50 ml of aqueous solution containing SDS (sodium dodecyl sulfate) (SDS concentration is 4 mg / ml), 500 mg of thioglycolic acid were added, and stirred at 500 rpm for 10 min at room temperature of 25°C.
[0182] The aqueous phase solution was mixed with the oil phase solution, stirred at 600 rpm for 30 min at room temperature of 25°C to emulsify into water-in-oil microdroplets. The mixture was stirred at 400 rpm at room temperature of 25°C for 16 h. The supernatant (solvent, surfactant, and excess thioglycolic acid) was removed by centrifugation, and then washed once with water, and 2 ml of saturated sodium chloride was added to precipitate the aqueous phase quantum dots to obtain aqueous phase quantum dots.
[0183] Comparative Example 8:
[0184] Preparation of oil phase solution: 400 mg of InP / ZnSeS / ZnS green quantum dots (with oleic acid and oleylamine on the surface) were mixed with 10 ml of chloroform, and stirred at 400 rpm for 10 min at room temperature of 25°C to mix evenly. Preparation of water phase solution: 50 ml of an aqueous solution containing SDS (sodium dodecyl sulfate) (the concentration of SDS is 4 mg / ml), 500 mg of thioglycolic acid was added, and stirred at 500 rpm for 10 min at room temperature of 25°C.
[0185] The aqueous phase solution and the oil phase solution were mixed, stirred at 600 rpm for 30 min at room temperature of 25°C to emulsify into water-in-oil microdroplets. The mixture was stirred at 400 rpm at room temperature of 25°C for 16 h. The supernatant was removed by centrifugation, and then washed once with water, and 2 ml of saturated sodium chloride was added to precipitate the aqueous phase quantum dots to obtain aqueous phase quantum dots.
[0186] Comparative Example 9:
[0187] Preparation of oil phase solution: 400 mg of CdSe / ZnSeS / ZnS red light quantum dots (with oleic acid and thiol on the surface) were mixed with 10 ml of chloroform, and stirred at 400 rpm for 10 min at room temperature of 25°C to mix evenly. Preparation of water phase solution: 50 ml of aqueous solution containing SDS (sodium dodecyl sulfate) (SDS concentration is 4 mg / ml), 500 mg of thioglycolic acid were added, and stirred at 500 rpm for 10 min at room temperature of 25°C.
[0188] The aqueous phase solution was mixed with the oil phase solution, stirred at 600 rpm for 30 min at room temperature of 25°C to emulsify into water-in-oil microdroplets. The mixture was stirred at 400 rpm at room temperature of 25°C for 16 h. The supernatant (solvent, surfactant, and excess thioglycolic acid) was removed by centrifugation, and then washed once with water, and 2 ml of saturated sodium chloride was added to precipitate the aqueous phase quantum dots to obtain aqueous phase quantum dots.
[0189] Comparative Example 10:
[0190] Preparation of oil phase solution: 400 mg of InP / ZnSeS / ZnS red light quantum dots (with oleic acid and thiol on the surface) were mixed with 10 ml of chloroform, and stirred at 400 rpm for 10 min at room temperature of 25°C to mix evenly. Preparation of water phase solution: 50 ml of an aqueous solution containing SDS (sodium dodecyl sulfate) (the concentration of SDS is 4 mg / ml), 500 mg of thioglycolic acid was added, and stirred at 500 rpm for 10 min at room temperature of 25°C.
[0191] The aqueous phase solution and the oil phase solution were mixed, stirred at 600 rpm for 30 min at room temperature of 25°C to emulsify into water-in-oil microdroplets. The mixture was stirred at 400 rpm at room temperature of 25°C for 16 h. The supernatant was removed by centrifugation, and then washed once with water, and 2 ml of saturated sodium chloride was added to precipitate the aqueous phase quantum dots to obtain aqueous phase quantum dots.
[0192] In the above Examples 1-14 and Comparative Examples 3-10, the weight of the obtained water-phase quantum dots was divided by the weight of the initial oily quantum dots to obtain the quantum dot water-phase conversion yield, and the data are shown in Table 1.
[0193] In the above Examples 1-14 and Comparative Examples 3-10, the initial oily quantum dots were dissolved in heptane so that the concentration of the oily quantum dots in water was 0.3 mg / ml; the obtained aqueous phase quantum dots were redissolved in water so that the concentration of the aqueous phase quantum dots in water was 0.3 mg / ml; and the photoluminescence quantum yield (QY) was detected using an integrating sphere efficiency tester (also known as a fluorescence quantum efficiency tester).
[0194] Table 1: The yield of water phase conversion, initial oily quantum dots and luminescence quantum yield of water phase quantum dots in Examples 1-14 and Comparative Examples 3-10.
[0195]
[0196]
[0197] Examples 1-7 are cadmium-based (IIB-VIA family representative) oily quantum dots transferred to water phase. Compared with comparative examples 3, 5, 7, and 9, it can be seen from the data in Table 1 that the water phase transfer yield and the luminescence quantum yield (QY) of the water phase quantum dots of the technical solution of the present application are significantly higher than those of the prior art. Examples 8-14 are indium phosphide-based (IIIA-VA family representative) oily quantum dots transferred to water phase. Compared with comparative examples 4, 6, 8, and 10, it can be seen from the data in Table 1 that the water phase transfer yield and the luminescence quantum yield (QY) of the water phase quantum dots of the technical solution of the present application are significantly higher than those of the prior art.
[0198] Although the present application has disclosed multiple aspects and embodiments, other aspects and embodiments will be obvious to those skilled in the art, and several modifications and improvements may be made without departing from the concept of the present application, all of which belong to the protection scope of the present application. The multiple aspects and embodiments disclosed in the present application are only for illustration and are not intended to limit the present application. The actual protection scope of the present application shall be subject to the claims.
Claims
1. A method for transferring oily quantum dots to an aqueous phase, characterized in that: The method comprises: S1, preparation of seed microspheres containing oily quantum dots encapsulated in amphiphilic polymers by self-assembly; S2, dissolving the seed microspheres in an aqueous solution, and adding a regulator to reduce the polarity of the outer surface of the seed microspheres or reduce the polarity of the aqueous solution; S3, adding a hydrophilic ligand into S2 to form a reaction mixture, wherein the hydrophilic ligand combines with the oily quantum dots to transfer the oily quantum dots to a water phase, thereby obtaining water phase quantum dots.
2. The method for transferring oily quantum dots to water phase according to claim 1, characterized in that: In step S1, one or more features selected from the following group are included: (1) The self-assembly refers to the physical interaction between the amphiphilic polymer and the oily quantum dots to form an amphiphilic polymer shell layer encapsulating the oily quantum dot seed microspheres; (2) The self-assembly refers to mixing an amphiphilic polymer, oily quantum dots, a non-polar solvent, water and an oil-in-water surfactant, emulsifying to form oil-in-water microdroplets, evaporating / volatizing the non-polar solvent, and forming seed microspheres containing a plurality of oily quantum dots encapsulated in the amphiphilic polymer; (3) The amphiphilic polymer comprises a hydrophilic segment and a lipophilic segment, wherein the hydrophilic segment is soluble in water solvent and the lipophilic segment is soluble in non-polar solvent; (4) The surface of the oily quantum dots has lipophilic groups.
3. The method for transferring oily quantum dots to water phase according to claim 1, characterized in that: In step S2, in the aqueous solution, the concentration of the seed microspheres is 1-30 mg / ml; the aqueous solution also includes: a dispersant.
4. The method for transferring oily quantum dots to water phase according to claim 1, characterized in that: In step S2, a regulator is added so that the absolute value of the difference between the polarity parameters inside and outside the amphiphilic polymer shell is smaller than the absolute value of the difference between the polarity parameters of the water phase quantum dots and the oil phase quantum dots; Preferably, in step S2, a regulator is added so that the absolute value of the difference in polarity parameters inside and outside the amphiphilic polymer shell is 5-7.
5.
5. The method for transferring oily quantum dots to water phase according to claim 4, characterized in that: The regulator includes at least one of an esterification catalyst, water-soluble aldehydes, water-soluble glycerol ethers, salts, and polar solvents.
6. The method for transferring oily quantum dots to water phase according to claim 5, characterized in that: Includes one or more features selected from the following group: (1) The esterification catalyst comprises: at least one of a water-soluble carbodiimide salt and a water-soluble imide salt, and the mass ratio of the esterification catalyst to the seed microspheres added to the aqueous solution in step S2 is 1:(2-10); (2) In the aqueous solution of step S2, the water-soluble aldehyde and the seed microspheres are added in a mass ratio of 1: (2-10), the water-soluble aldehydes include at least one of glutaraldehyde, acetaldehyde, succinaldehyde, and adipaldehyde; (3) In the aqueous solution of step S2, the mass ratio of the water-soluble glyceryl ether to the seed microsphere is 1:(2-10); the water-soluble glyceryl ether includes at least one of diglycidyl ether, propenyl glycidyl ether, glycerol triglycidyl ether, and butanediol diglycidyl ether; (4) In the aqueous solution of step S2, the mass ratio of the salt added is 0.3-0.5 mg / ml, and the salt includes at least one of sodium chloride, potassium chloride, sodium bicarbonate, sodium carbonate, and calcium chloride; (5) The dielectric constant of the polar solvent is ≥18. In the aqueous solution of step S2, the mass ratio of the polar solvent to water is 1:(10-100).
7. The method for transferring oily quantum dots to water phase according to claim 1, characterized in that: In step S3, the hydrophilic ligand includes: a coordination group and a hydrophilic group, the coordination group can be connected to the surface of the oily quantum dots, and the hydrophilic group provides hydrophilicity for the quantum dots; the molecular weight of the hydrophilic ligand is 50-400.
8. The method for transferring oily quantum dots to water phase according to claim 1, characterized in that: The luminescence quantum yield of the water phase quantum dots is ≥88%, and the water phase conversion yield of the oily quantum dots is ≥85%.
9. A water-phase quantum dot, characterized in that: The water phase quantum dots are obtained by the method for converting oil phase quantum dots to water phase as described in any one of claims 1-8.
10. The aqueous phase quantum dot according to claim 9, characterized in that: The luminescence quantum yield of the water-phase quantum dots is ≥88%.